2019
DOI: 10.3390/foods8120646
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Phytochemical Composition and Biological Activities of Differently Pigmented Varieties of Berry Fruits; Comparison between Embedded in Food Matrix and Isolated Anthocyanins

Abstract: The aim of this research was to correlate the composition of phenolic compounds and bioactivities (antioxidant, cytotoxic, antigenotoxic, and influence on selected enzymatic activities) exhibited by extracts from differently pigmented raspberry (yellow and red), grape (white and red), mulberry (white and black), and currant (white, red, and black) varieties. It was presumed that phytocomplexes of the same species will be similar while differing significantly only by the content of anthocyanins in colored varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 38 publications
0
28
1
Order By: Relevance
“…This fact is not surprising considering the reports in the literature about the positive correlation between the content of redox-active compounds—particularly the phenols and anthocyanins of berry extracts—and DPPH and FRAP in vitro assays [ 45 ]. The DPPH IC50 values of samples in this work were higher than those reported in enzymatically treated anthocyanin fractions of the raspberry pomace [ 54 ]. In general, TPC, TFC, and particularly TAC, as well as their respective antioxidant activities in terms of DPPH and FRAP assays, appear to be higher in the raspberry fruit extracts obtained with the help of ultrasound (UAE) in contrast to simple conventional maceration (CM) [ 51 , 52 , 55 ].…”
Section: Resultscontrasting
confidence: 63%
“…This fact is not surprising considering the reports in the literature about the positive correlation between the content of redox-active compounds—particularly the phenols and anthocyanins of berry extracts—and DPPH and FRAP in vitro assays [ 45 ]. The DPPH IC50 values of samples in this work were higher than those reported in enzymatically treated anthocyanin fractions of the raspberry pomace [ 54 ]. In general, TPC, TFC, and particularly TAC, as well as their respective antioxidant activities in terms of DPPH and FRAP assays, appear to be higher in the raspberry fruit extracts obtained with the help of ultrasound (UAE) in contrast to simple conventional maceration (CM) [ 51 , 52 , 55 ].…”
Section: Resultscontrasting
confidence: 63%
“…Fruits and vegetables contain many different phytochemicals [ 1 , 2 ]. Many studies have reported the higher intake of fruits and vegetables can reduce the risk of developing chronic disease [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier study verified this concept by comparing bioactivities of real foods with their isolated major antioxidant. This showed that the biological effects of extracts of berry fruits vastly differ from those exhibited by anthocyanin cyanidin-3- O -glucoside 12 . Some other reports also indicated the importance of the interactions between different bioactive compounds and food matrix components that turned out to be cooperating factors, which determine the final bioactivity of foods 13 17 .…”
Section: Introductionmentioning
confidence: 98%